Purification, crystallization and preliminary X-ray analysis of a hexameric β-glucosidase from wheat - Sue, Masayuki (International Union of Crystallography, 2005)
The wheat β-glucosidase TaGlu1b, which is only active in a hexameric form, was tagged with 6×His at the N-terminus, overexpressed in Escherichia coli and purified in two steps. The protein complexed with a substrate aglycone was crystallized at 293 K from a solution containing 10 mM HEPES pH 7.2, 1 M LiSO(4) and 150 mM NaCl using the hanging-drop vapour-diffusion method. Diffraction data were collected to 1.7 Å at the Photon Factory. The crystal belongs to space group P4(1)32, with unit-cell parameters a = b = c = 194.65 Å, α = β = γ = 90°. The asymmetric unit was confirmed by molecular-replacement solution to contain one monomer, giving a solvent content of 72.1%.